Efecto del aceite esencial de orégano (Oreganum vulgare L.) como agente antimicrobiano en la conservación de la carne de dos especies de tilapia: negra (Oreochromis mossambicus) y roja (Oreochromis niloticus) - Mera Mendoza, César Rolando (2015)
The objective of this investigation was to evaluate the effect of the essential oil of oregano as an antimicrobial agent in the conservation of the meat of two species of tilapia, with the aim to enhance the addition of natural preservatives in the meat. We used 24 tilapia fillet, samples were taken from 50 and 150 grams for 12 treatments and 2 repetitions. In the statistical analysis used a factorial arrangement of blocks with 2 repetitions AxBxC recital as factor A: species of tilapia (Oreochromis mossambicus and Oreochromis niloticus), factor B: concentrations of essential oil of oregano (1 %, 3% and 5 %), factor C: concentrations of sodium chloride (10% and 20 %); was also characterized the chemical components of essential oil of oregano by gas chromatography. For the analysis of data was performed using statistical package Statgraphics, in addition to the separation of half of the levels of the treatments she went to the test of significance of Tukey (p<0.05). In the evaluation of therapies it was concluded that there was a significant difference between the levels of the treatments. As a result it was determined that the best treatment was the a1b2c1 (O. niloticus * 5% AEO * 20% ClNa); since it introduced the best values (3x105) in the content of aerobic microorganisms. Key words: tilapia, essential oil, oregano, sodium chloride.